Composition for electrostatic dissipation coating, polarizing plate, and optical display device
By using a curable resin with carboxylic acid groups, a bifunctional aziridine curing agent and a conductive polymer composition, the stability and adhesion of the electrostatic dissipative coating under high temperature and high humidity conditions is solved, and the stability and adhesion of the electrostatic dissipative coating is achieved. Electrostatic dissipation coating with uniform electrostatic dissipation and high reliability.
Patent Information
- Application Number
- CN202411395607.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2016-12-09
- Filing Date
- 2017-12-04
- Publication Date
- 2025-01-07
AI Technical Summary
When forming an electrostatic dissipation coating, there are problems with stability and environmental protection caused by saponification of high concentration alkali solution. The surface resistance changes greatly, the adhesion is insufficient, and the electrostatic damage is easy to cause LCD abnormality, making it difficult to be high at high temperatures. Maintain performance under wet conditions.
Using a composition of a curable resin with carboxylic acid groups, a bifunctional aziridine curing agent and a conductive polymer, an electrostatic dissipation with a long-lasting and good adhesion is formed by a combination of specific curing and adhesives. Coating ensures stability and electrostatic dissipation performance under room temperature and high temperature and high humidity conditions.
It realizes the durability and stability of the electrostatic dissipation coating under high temperature and high humidity conditions, reduces the surface resistance change rate, ensures good adhesion to the polarizing film and adhesive layer and uniform electrostatic dissipation effect, and improves the The reliability of LCD.
Smart Images

Figure CN119264805A_ABST
Abstract
Description
[0001] This application is a divisional application of an invention patent application with an application date of December 4, 2017, application number 201711259880.4, and invention name “Composition for electrostatic dissipative coating, polarizing plate and optical display device”.
[0002] Citations of Related Applications
[0003] This application claims the benefit of Korean Patent Application No. 10-2016-0167990 filed on December 9, 2016, in the Korean Intellectual Property Office, the disclosure of which is incorporated herein in its entirety by reference. Technical Field
[0004] The present invention relates to a composition for a static dissipative coating layer, a polarizing plate (polarizing plate) comprising the composition, and an optical display comprising the polarizing plate. More particularly, the present invention relates to a composition for a static dissipative coating, which has a long pot-life to provide good coating processability, exhibits good durability and small surface resistance change under high temperature / high humidity conditions, can ensure good adhesion to a polarizing film and / or an adhesive layer at room temperature and under high temperature / high humidity conditions, and can achieve a static dissipative coating with uniform static dissipative properties. The present invention also relates to a polarizing plate comprising the composition and an optical display comprising the polarizing plate. Background Art
[0005] Generally, polarizing film includes cellulose resin film bonded on two surfaces of polarizer formed by polyvinyl alcohol resin. Polarizing film generally has a multilayer structure, wherein a protective film is bonded to one surface of the polarizer to prevent surface damage during transportation, and an adhesive layer and a release film are stacked on the other surface thereof. Polarizing plate is used as a main component of a liquid crystal display (LCD). In order to ensure the high reliability and high durability of using polarizing film under various conditions, it is necessary to ensure the strong bonding between polarizer and resin film. In a method for enhancing bonding between them, a triacetyl cellulose film used as a resin film is saponified with an alkaline solution, and then bonded to the polarizer using a polyvinyl alcohol adhesive.
[0006] However, since a high concentration of alkaline solution is used for saponification treatment, it is undesirable in terms of working stability and environmental protection. In addition, saponification treatment with an alkaline solution makes the surface of the film hydrophilic, resulting in a significant decrease in the contact angle, and surface treatment with a hydrophobic resin can lead to deterioration of adhesion. In addition, when saponification treatment is performed after surface treatment (such as antistatic treatment and hard coating treatment) for imparting various functions, there is a problem that the surface treatment layer may dissolve in the alkaline solution or may reduce the surface treatment effect.
[0007] On the other hand, when attaching a polarizing film to a liquid crystal display (LCD), after removing the release film, the polarizing film is attached to the surface of the LCD. In this case, the polarizing film may be damaged by static electricity when removing the release film or separating the protective film. In addition, when there is foreign matter between the layers, the LCD may encounter problems such as abnormal images, abnormal liquid crystal display, or abnormal operation on the liquid crystal display screen. In particular, since the LCD has a multi-layer stacking structure, during operation, if static electricity is generated or foreign matter exists even in a part of the entire stacking structure, the entire LCD will be damaged.
[0008] Therefore, various methods such as forming a conductive layer on a triacetyl cellulose film, using a conductive adhesive or binder, using a protective film having conductivity, etc. are used as charge prevention techniques. However, the film formed by this technique exhibits insufficient optical properties such as transparency or insufficient adhesion to other films. In addition, the film cannot be effectively used due to performance degradation caused by the influence of temperature or moisture, bubbling, etc. In addition, although a surfactant can be deposited on a triacetyl cellulose film when forming a conductive layer on the triacetyl cellulose film, this method has the problem of significant dependence of charge prevention on humidity, and provides insufficient effect at low humidity.
[0009] The background art of the present invention is disclosed in Korean Patent No. 0760978. Summary of the invention
[0010] An object of the present invention is to provide a composition for static dissipative coating, which has a static dissipative effect and a long pot life, provides good storage stability to improve processability.
[0011] Another object of the present invention is to provide a composition for static dissipative coatings that can form static dissipative coatings having good durability and small changes in surface resistance under high temperature / high humidity conditions.
[0012] Another object of the present invention is to provide a composition for static dissipative coating, which exhibits good adhesion to a polarizing film and / or an adhesive layer not only at room temperature but also under high temperature / high humidity conditions and is capable of forming a static dissipative coating providing a uniform static dissipative effect.
[0013] Yet another object of the present invention is to provide a composition for static dissipative coatings that is capable of forming an optically clear static dissipative coating.
[0014] Still another object of the present invention is to provide a polarizing plate including a static dissipative coating formed of the composition for a static dissipative coating according to the present invention.
[0015] Still another object of the present invention is to provide an optical display comprising a static dissipative coating formed from the composition for a static dissipative coating according to the present invention.
[0016] According to one aspect of the present invention, a composition for a static dissipative coating may include: a curable resin having a carboxylic acid group, a bifunctional aziridine (dimethylimine) curing agent, and a conductive polymer.
[0017] In one embodiment, the composition for static dissipative coating has an initial standing time of 24 hours or more, for which the difference in the common logarithm of the surface resistance expressed by the following Formula 2 is 2Ω / □ or more:
[0018] <Formula 2>
[0019] |log 10 A-log 10 B|
[0020] (wherein, B is the surface resistance value (unit: Ω / □) of the composition for static dissipative coating measured on a 0.1 μm thick first coating layer under the conditions of 23° C. and 55% relative humidity (RH), wherein the first coating layer is obtained by coating 100 g of the composition on a polarizing film to a thickness of 10 μm, followed by drying at 80° C. for 2 minutes, and
[0021] A is the surface resistance value (unit: Ω / □) of the composition for static dissipative coating measured on a 0.1 μm thick second coating layer under the conditions of 23°C and 55% RH, wherein the second coating layer is obtained by placing 100 g of the composition at 25°C for a predetermined period of time and coating the composition on a polarizing film to a thickness of 10 μm, followed by drying at 80°C for 2 minutes).
[0022] In one embodiment, the curable resin may have an acid value of about 1 to about 30 mg KOH / g.
[0023] In one embodiment, the curable resin may be a thermally curable resin having a (meth)acrylate group.
[0024] In one embodiment, the curable resin may contain a urethane bond.
[0025] In one embodiment, the curable resin may include polyurethane (meth) acrylate including a carboxylic acid group.
[0026] In one embodiment, the conductive polymer may be doped with a water-based dopant.
[0027] In one embodiment, the conductive polymer may include at least one of polyacetylene, poly(p-phenylene), polythiophene, poly(3,4-ethylenedioxythiophene), polypyrrole, poly(p-phenylene sulfide), poly(p-phenylene vinylene), poly(thienylene vinylene), and polyaniline.
[0028] In one embodiment, the bifunctional aziridine curing agent may include at least one of N,N'-(methylenediphenylene)bis(aziridine-1-carboxamide) and N,N'-hexamethylene 1,6-bis(1-aziridinecarboxamide).
[0029] In one embodiment, the composition for the static dissipative coating may be a water-based composition including a water-based solvent.
[0030] In one embodiment, the water-based solvent may be (i) water, or (ii) a mixed solvent including water and at least one of alcohol and dimethyl sulfoxide.
[0031] In one embodiment, the composition for static dissipative coating may include 80 to 99 parts by weight of a curable resin having a carboxylic acid group, 1 to 20 parts by weight of a conductive polymer, and 0.0005 to 0.02 parts by weight of a difunctional aziridine curing agent, relative to 100 parts by weight of the curable resin having a carboxylic acid group and the conductive polymer.
[0032] According to another aspect of the present invention, a polarizing plate comprises: a polarizing film, a static dissipative coating layer, and an adhesive layer, wherein the static dissipative coating layer is formed of the composition for static dissipative coating layer according to the present invention.
[0033] In one embodiment, the polarizing plate may have a surface resistance variation rate of 5% or less calculated by the following Equation 1:
[0034] <Equation 1>
[0035] Surface resistance change rate = |R1-R0| / R0 x 100
[0036] (wherein R0 is the initial surface resistance value (unit: Ω / □) measured on the adhesive layer of the polarizing plate under the conditions of 23°C and 55% RH, and
[0037] R1 is a surface resistance value (unit: Ω / □) measured on the adhesive layer of the polarizing plate at room temperature by the same method as above after the polarizing plate was left under conditions of 60° C. and 95% RH for 500 hours.
[0038] In one embodiment, the static dissipative coating may be formed directly on the polarizing film.
[0039] In one embodiment, the static dissipative coating may have a thickness of 1 nm to 10 μm.
[0040] In one embodiment, the adhesive layer may be formed of an adhesive composition including a (meth)acrylate copolymer having a carboxylic acid group and a curing agent.
[0041] According to a further aspect of the present invention, an optical display may include the composition for static dissipative coating according to the present invention or the polarizing plate according to the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 is a cross-sectional view of a polarizing plate according to one embodiment of the present invention. DETAILED DESCRIPTION
[0043] Embodiments of the present invention will be described in detail with reference to the accompanying drawings. The following embodiments are provided to provide a complete disclosure of the present invention and a thorough understanding of the present invention to those skilled in the art. It should be understood that the present invention is not limited to the following embodiments and can be implemented in different ways. The accompanying drawings are not drawn precisely to scale and some dimensions such as width, length, thickness, etc. are exaggerated for clarity of description. Throughout the accompanying drawings, the same components will be represented by the same reference numerals.
[0044] In this document, spatial relative terms such as "upper" and "lower" are defined with reference to the accompanying drawings. Therefore, it should be understood that the term "upper surface" can be used interchangeably with the term "lower surface".
[0045] As used herein, the term "(meth)acryloyl" refers to acryloyl and / or methacryloyl.
[0046] Herein, the term "pot life" refers to an initial period of time during which the difference between the common logarithms of the surface resistance expressed by the following Formula 2 becomes 2Ω / □ or more, preferably 2Ω / □:
[0047] <Formula 2>
[0048] |log 10 A-log 10 B|
[0049] Wherein, B is the surface resistance value (unit: Ω / □) of the composition for static dissipative coating measured on a 0.1 μm thick first coating layer under the conditions of 23° C. and 55% RH, wherein the first coating layer is obtained by coating 100 g of the composition on a polarizing film to a thickness of 10 μm, followed by drying at 80° C. for 2 minutes, and
[0050] A is the surface resistance value (unit: Ω / □) of the composition for static dissipative coating measured on a 0.1 μm thick second coating layer under the conditions of 23°C and 55% RH, wherein the second coating layer is obtained by placing 100 g of the composition at 25°C for a predetermined period of time and coating the composition on a polarizing film to a thickness of 10 μm, followed by drying at 80°C for 2 minutes.
[0051] Herein, the term "surface resistance change rate" is measured relative to a polarizing plate, wherein a static dissipative coating (thickness: 0.1 μm to 0.2 μm) is formed on one surface of a triacetyl cellulose film of a polarizing film, the polarizing film having a three-layer structure including triacetyl cellulose films stacked on both surfaces of a polarizer formed of a polyvinyl alcohol resin, and an adhesive layer (acrylic adhesive layer, thickness: 20 μm) is formed on one surface of the static dissipative coating. The acrylic adhesive layer is formed of a typical acrylic adhesive, and its composition is not limited to a specific composition. A low surface resistance change rate indicates high reliability by preventing degradation of the static dissipative function, even if the polarizing plate is exposed to high temperature / high humidity conditions for a long time:
[0052] <Equation 1>
[0053] Surface resistance change rate = |R1-R0| / R0 x 100
[0054] (where R0 is the initial surface resistance value (unit: Ω / □) measured on the adhesive layer of the polarizing plate under the conditions of 23°C and 55% RH, and
[0055] R1 is a surface resistance value (unit: Ω / □) measured on the adhesive layer of the polarizing plate at room temperature by the same method as above after the polarizing plate was left under conditions of 60° C. and 95% RH for 500 hours.
[0056] Next, a composition for static dissipative coating according to one embodiment of the present invention will be described.
[0057] The composition for static dissipative coating according to this embodiment may include a curable resin having a carboxylic acid group (hereinafter, "curable resin"), a conductive polymer, and a bifunctional aziridine curing agent.
[0058] The curable resin may be cured alone or by a difunctional aziridine curing agent to form the matrix of the static dissipative coating.
[0059] Curable resin can include curable resin with carboxylic acid group (-COOH).Carboxylic acid group reacts with aziridine group of bifunctional aziridine curing agent to improve the curing rate of the composition for static dissipative coating.In addition, carboxylic acid group can improve the adhesion between bonding layer and static dissipative coating in polarizing plate.Static dissipative coating is non-bonding layer.When bonding layer is formed by (meth) acrylic adhesive resin with carboxylic acid group, bifunctional aziridine curing agent allows curable resin of static dissipative coating and (meth) acrylic adhesive resin of bonding layer to be cured simultaneously, thereby improving the adhesion between static dissipative coating and bonding layer.
[0060] The curable resin having a carboxylic acid group may exhibit an acid value in a predetermined range. For example, the curable resin may have an acid value of 1.0 mg KOH / g to 30 mg KOH / g, preferably 5.0 mg KOH / g to 15 mg KOH / g. Within this range of the acid value of the curable resin, the composition may ensure good durability and prevent degradation of static dissipative properties.
[0061] The curable resin is a heat-curable resin and may contain a heat-curable functional group. For example, the heat-curable functional group may be a (meth)acrylate group, but is not limited thereto. When a (meth)acrylic adhesive resin is used as an adhesive resin for an adhesive layer of a surface of a static dissipative coating to be attached to a polarizing plate, the adhesion between the static dissipative coating and the adhesive layer may be improved by a reaction between (meth)acrylate groups. Preferably, the curable resin includes a pentafunctional or higher functional (meth)acrylic adhesive resin, such as a pentafunctional to ten-functional (meth)acrylic adhesive resin. Within this range, the curable resin can ensure improved durability.
[0062] The curable resin has a urethane bond, thereby improving durability by preventing local stress in the static dissipative coating layer caused by shrinkage and expansion of the polarizing film.
[0063] The weight average molecular weight of the curable resin may be 3,000 g / mol or greater. For example, the weight average molecular weight of the curable resin may be 3,000 g / mol to 100,000 g / mol, 3,000 g / mol to 80,000 g / mol, 3,000 g / mol to 10,000 g / mol or 3,000 g / mol to 8,000 g / mol. Within this weight average molecular weight range, the curable resin can maintain good dispersibility in a water-based solvent. The weight average molecular weight can be obtained by gel permeation chromatography according to a polystyrene standard. The glass transition temperature of the curable resin may be -60°C to 0°C, specifically -45°C to -5°C. Within this range, the curable resin may have fluidity and may ensure good durability. The polydispersity index of the curable resin may be 2.5 to 9.0, specifically 3 to 6. Within this range, the curable resin allows stable polymerization and may prevent degradation of durability.
[0064] Although not particularly limited, the solubility of the curable resin in the water-based solvent is low so as to allow the composition for the static dissipative coating to be used as a water-based composition. In this article, the term "water-based solvent" refers to a solvent containing 50 wt% or more of water. The water-based solvent may include water, alcohols (such as isopropyl alcohol, ethanol and ethoxyethanol), dimethyl sulfoxide, etc.
[0065] In one embodiment, the curable resin may include urethane (meth) acrylate containing a carboxylic acid group. The urethane (meth) acrylate may be prepared by a typical method.
[0066] For example, the prepolymer with urethane bond is prepared by polymerization of difunctional or higher polyfunctional polyol and difunctional or higher polyfunctional isocyanate. The polyfunctional polyol may include at least one of aliphatic polyol, alicyclic polyol and aromatic polyol. The polyfunctional polyol may include at least one of polyester polyol, polycarbonate polyol, polyolefin polyol, polyether polyol, polythioether polyol, polysiloxane polyol, polyacetal polyol and polyesteramide polyol, but is not limited thereto. For example, the polyfunctional polyol may include polyhydroxy polyols such as neopentyl glycol, 3-methyl-1,5-pentanediol, ethylene glycol, propylene glycol, 1,4-butanediol, 1,6-hexanediol, trimethylolpropane, pentaerythritol, and tricyclodecane dihydroxymethyl; polyester polyols obtained by reaction between polyols and polyacids; polycaprolactone polyols and polycaprolactone glycols obtained by reaction between polyols and ε-caprolactone; polycarbonate polyols obtained by reaction between 1,6-hexanediol and diphenyl carbonate; and polyether polyols such as polyethylene glycol, polypropylene glycol, polytetramethylene glycol, and bisphenol A modified by ethylene oxide, but are not limited thereto. The polyfunctional isocyanate may include certain aliphatic, alicyclic, or aromatic isocyanates. For example, the polyfunctional isocyanate may include methylene diphenyl diisocyanate, isophorone diisocyanate, hexamethylene diisocyanate, toluene diisocyanate, xylene diisocyanate, and dicyclopentane diisocyanate, but is not limited thereto.
[0067] In the preparation of the prepolymer, a tin compound, such as a tin salt of a carboxylic acid, such as dibutyltin dilaurate, or an amine compound, such as dimethylcyclohexylamine or triethylenediamine, may be further included as a catalyst to promote the formation of a carbamate bond. In the preparation of the prepolymer, a diol (such as an aliphatic diol), an amino alcohol, a diamine, a hydrazine, a hydrazide or a mixture thereof may be further included as a chain extender for extending the chain of the prepolymer. The preparation of the prepolymer may be carried out at 50° C. to 200° C. for 30 minutes to 10 hours. Within this range, the prepolymer may be prepared in high yield.
[0068] Then, by polymerizing the (meth) acrylic monomers without carboxylic acid groups with the prepared prepolymer, and then polymerizing with the (meth) acrylic monomers containing carboxylic acid groups, polyurethane (meth) acrylates containing carboxylic acid groups can be prepared. The (meth) acrylic monomers without carboxylic acid groups can include typical monomers, such as methyl (meth) acrylate, etc. The (meth) acrylic monomers containing carboxylic acid groups are monomers having a carboxyl group and a (meth) acrylate group, such as (meth) acrylic acid. The (meth) acrylic monomers containing carboxylic acid groups can be prepared by typical methods well known to those skilled in the art. A polymerization inhibitor can be further added to produce a desired amount of carboxylic acid groups after the (meth) acrylic monomers containing carboxylic acid groups are polymerized.
[0069] By controlling the amount of the (meth)acrylic monomer containing a carboxylic acid group among the polyfunctional polyol, the polyfunctional isocyanate and the (meth)acrylic monomer containing a carboxylic acid group, a curable resin having an acid value within the above range can be obtained.
[0070] Among the polyfunctional polyol, the polyfunctional isocyanate, the (meth) acrylic monomer and the (meth) acrylic monomer containing a carboxylic acid group, the (meth) acrylic monomer containing a carboxylic acid group may be present in an amount of 0.1 wt % to 5 wt %. Within this range, the composition may ensure good performance in terms of durability, storage stability and electrostatic dissipation performance.
[0071] The curable resin may be present in an amount of 80 to 99 parts by weight, for example 85 to 95 parts by weight, specifically 88 to 93 parts by weight, relative to 100 parts by weight of the curable resin and the conductive polymer. Within this range, the curable resin can ensure coating stability and durability.
[0072] Although the conductive polymer does not undergo a curing reaction with the curable resin and the difunctional aziridine curing agent, the conductive polymer can provide static dissipative functionality to the static dissipative coating.
[0073] The conductive polymer may include typical conductive polymers well known to those skilled in the art. For example, the conductive polymer may include at least one of polyacetylene, poly(p-phenylene), polythiophene, poly(3,4-ethylenedioxythiophene), polypyrrole, poly(p-phenylene sulfide), poly(p-phenylene vinylene), poly(thienyl vinylene), and polyaniline.
[0074] Although the conductive polymer may be contained in the composition for static dissipative coating itself, the conductive polymer may be added to the composition for static dissipative coating as a liquid dispersion containing the conductive polymer. When the composition for static dissipative coating contains a water-based solvent, the conductive polymer may further contain a water-based dopant, such as polystyrene sulfonate. Preferably, the conductive polymer comprises poly(3,4-ethylenedioxythiophene) doped with polystyrene sulfonate.
[0075] The conductive polymer may be present in an amount of 1 to 20 parts by weight, for example 5 to 15 parts by weight, specifically 7 to 12 parts by weight, relative to 100 parts by weight of the curable resin and the conductive polymer. Within this range, the composition may satisfy optical properties and electrostatic dissipation properties.
[0076] The bifunctional aziridine curing agent can increase the crosslinking density and / or storage modulus of the static dissipative coating by reacting with the curable resin (especially the carboxylic acid group of the curable resin), thereby improving the durability of the polarizing plate even after long-term storage under harsh conditions such as high temperature / high humidity.
[0077] The bifunctional aziridine curing agent can improve the storage stability, workability and processing properties of the composition for the static dissipative coating by extending the pot life of the composition for the static dissipative coating. Specifically, the composition according to the present invention can have a pot life of 24 hours or longer (e.g., 24 hours to 36 hours). Although the trifunctional aziridine curing agent can relatively reduce the pot life, even trace amounts of aziridine curing agents provide poor durability under high temperature / high humidity conditions.
[0078] The bifunctional aziridine curing agent may include a curing agent having two aziridine groups, for example, the bifunctional aziridine curing agent may include at least one of N,N'-(methylene di-p-phenylene)bis(aziridine-1-carboxamide) and N,N'-hexamethylene 1,6-bis(1-aziridine carboxamide), but is not limited thereto.
[0079] The difunctional aziridine curing agent may be present in an amount of 0.0005 to 0.02 parts by weight, such as 0.001 to 0.02 parts by weight, specifically 0.001 to 0.015 parts by weight, relative to 100 parts by weight of the curable resin and the conductive polymer. Within this range, the composition for the static dissipative coating can ensure application life and durability.
[0080] The composition for the static dissipative coating may further include a solvent to improve its coverage. For example, the solvent may include a water-based solvent, an organic solvent, etc. For example, the water-based solvent may be (i) water, or (ii) a mixed solvent including at least one of an alcohol and dimethyl sulfoxide and water. For example, the solvent may be a water-based solvent, or a mixed solvent in which water and an alcohol are mixed in a weight ratio of 1:0.5 to 1:1, which takes into account the aqueous liquid dispersion of the curable resin and the conductive polymer.
[0081] The composition for the static dissipative coating may further include a thermal initiator. The thermal initiator can increase the curing initiation rate when the composition for the static dissipative coating is thermally cured. The thermal initiator can be a peroxyester compound, such as bis(4-butylcyclohexyl) peroxydicarbonate, diethoxyethyl peroxydicarbonate, diethoxyhexyl peroxydicarbonate, hexyl peroxydicarbonate, dimethoxybutyl peroxydicarbonate, bis(3-methoxy-3-methoxybutyl peroxydicarbonate), hexyl peroxypivalate, pentyl peroxypivalate, butyl peroxypivalate, or trimethylhexanoyl peroxide; an azo compound, such as 2,2-azobis-2,4-dimethylvaleronitrile, 2,2-azobisisobutyronitrile or 2,2-azobis-2-methylbutyronitrile; or an acyl peroxide, such as 3,5,5-trimethylhexanoyl peroxide, lauryl peroxide or dibenzoyl peroxide, but is not limited thereto.
[0082] The composition for static dissipative coating may further include typical additives. For example, the additives may include UV absorbers, antioxidants, defoamers, and pigments, but are not limited thereto.
[0083] The composition for a static dissipative coating may have a viscosity of 5 cP to 20 cP at 25° C. Within this range, the composition may have high coating property and covering property.
[0084] The composition for static dissipative coating can be used to form a static dissipative coating. For example, the composition for static dissipative coating can be applied to certain adherends (polarizing film, polarizer, delay film, protective film, etc.) or release films (polyethylene terephthalate film, triacetyl cellulose film, etc.), and then cured at 50° C. to 150° C. for 1 minute to 30 minutes to form a static dissipative coating.
[0085] Next, the polarizing plate according to the present invention will be described. The polarizing plate according to the present invention may include a static dissipative coating formed by the composition for static dissipative coating according to the present invention. With this structure, the polarizing plate can exhibit good durability, low surface resistance change rate, and good adhesion between the static dissipative coating and the polarizing film and / or adhesive layer under high temperature / high humidity conditions, and can ensure uniform static dissipative performance, providing high reliability.
[0086] Will refer to Figure 1 A polarizing plate according to one embodiment of the present invention is described. Figure 1 is a cross-sectional view of a polarizing plate according to one embodiment of the present invention.
[0087] See also Figure 1 , a polarizing plate 100 according to one embodiment includes a polarizing film 110 , a static dissipative coating layer 120 , and an adhesive layer 130 , which are sequentially stacked in the stated order.
[0088] The static dissipative coating 120 can provide a static dissipative function for the polarizing plate. The static dissipative coating 120 can be directly formed on the polarizing film 110. In this article, "directly formed on..." means that some adhesive layer, coating, etc. are not provided between the polarizing film 110 and the static dissipative coating 120.
[0089] The static dissipative coating 120 can be formed by a composition for a static dissipative coating according to the present invention. For example, the composition for a static dissipative coating can be coated on a polarizing film 110 and then cured at 50°C to 150°C for 1 minute to 30 minutes to form a static dissipative coating 120. The static dissipative coating can have a thickness of 1nm to 10μm. For example, the thickness of the static dissipative coating can be 50nm to 1μm, specifically 50nm to 500nm. Within this thickness range, the static dissipative coating can provide a static dissipative function and can be used for an optical display. The total light transmittance of the static dissipative coating in the visible light range can be 90% or greater, for example 90% to 99%. Within this range, the static dissipative coating can be used for an optical display.
[0090] Although the static dissipative coating 120 is a non-adhesive coating, the static dissipative coating 120 is attached to the polarizing film to provide a static dissipative function to the polarizing plate.
[0091] When the surface resistance measured on the static dissipative coating 120 at 25°C and 55% RH is defined as C, log 10 C can be in the range of 6.0Ω / □ to 11.0Ω / □. For example, log 10 C may be in the range of 7.0Ω / □ to 10.0Ω / □. Within this range, the polarizing plate may have a static dissipation function to prevent the LCD panel from being damaged due to static electricity applied to the LCD panel.
[0092] In the structure in which the static dissipative coating 120 is applied on the polarizing plate, the surface resistance change rate of the polarizing plate calculated by Equation 1 may be 5.0% or less, for example, 2.5% or less. Within this range, the polarizing plate does not suffer from degradation of the static dissipative function and can provide high reliability even when left under high temperature / high humidity conditions for a long time.
[0093] The polarizing film 110 is formed on the adhesive layer 130 and the light exiting surface of the static dissipative coating 120 , and polarizes the light passing through the static dissipative coating 120 .
[0094] The polarizing film 110 may include a separate polarizer or may further include a protective layer formed on at least one surface of the polarizer. In one embodiment, the polarizing film may be a polarizer. In another embodiment, the polarizing film may include a polarizer and a protective layer formed on one surface of the polarizer (i.e., on the light exit surface of the polarizer). In a further embodiment, the polarizing film may include a polarizer and a protective layer formed on both surfaces of the polarizer.
[0095] The polarizer may include a polyvinyl alcohol polarizer produced by dyeing a polyvinyl alcohol film with iodine or the like. For example, the polyvinyl alcohol film is dyed with iodine or a dichroic dye, and then the polyvinyl alcohol film is stretched in a certain direction to produce a polyvinyl alcohol polarizer. Specifically, the polyvinyl alcohol polarizer is produced by swelling, dyeing and stretching. Methods for performing these processes are well known in the art. The thickness of the polarizer may be from about 5 μm to about 50 μm. Within this thickness range, the polarizer may be used for an optical display.
[0096] The protective layer is formed on the polarizer to protect the polarizer and improve the mechanical strength of the polarizing film.
[0097] The protective layer may include at least one of an optically transparent protective film and a protective coating.
[0098] In a structure in which the protective layer is implemented by a protective film, the protective layer may include a protective film formed of an optically transparent resin. The protective film may be formed by melt extrusion of the resin. Further stretching treatment may be performed as needed. The resin may include at least one selected from the following: cellulose ester resins, including triacetyl cellulose, etc.; cyclic polyolefin resins, including amorphous cyclic olefin polymers (COP), etc.; polycarbonate resins; polyester resins, including polyethylene terephthalate (PET), etc.; polyether sulfone resins; polysulfone resins; polyamide resins; polyimide resins; non-cyclic polyolefin resins; polyacrylate resins, including poly (methyl methacrylate), etc.; polyvinyl alcohol resins; polyvinyl chloride resins and polyvinylidene chloride resins.
[0099] In a structure where the protective layer is implemented by a protective coating, the protective layer can improve adhesion, transparency, mechanical strength, thermal stability, moisture resistance and durability relative to the polarizer. In one embodiment, the protective coating for the protective layer is formed of an actinic radiation curable resin composition, which includes an actinic radiation curable compound and a polymerization initiator.
[0100] The actinic radiation curable compound may include at least one selected from a cationically polymerizable curable compound, a free radical polymerizable curable compound, a polyurethane resin, and a silicone resin. The cationically polymerizable curable compound may include at least one of an epoxy compound containing at least one epoxy group therein and an oxetane compound containing at least one oxetane ring therein. The free radical polymerizable curable compound may be a (meth) acrylic compound having at least one (meth) acryloyloxy group therein.
[0101] The epoxy compound may include at least one selected from the group consisting of a hydrogenated epoxy compound, a linear aliphatic epoxy compound, an alicyclic epoxy compound, and an aromatic epoxy compound.
[0102] The free radical polymerizable curable compound can realize a protective coating showing excellent performance in terms of hardness, mechanical strength and durability. The free radical polymerizable curable compound can be obtained by reacting a (meth)acrylate monomer having at least one (meth)acryloyloxy group with two or more functional group-containing compounds, and can include a (meth)acrylate oligomer having at least two (meth)acryloyloxy groups therein.
[0103] Examples of the (meth)acrylate monomer include a monofunctional (meth)acrylate monomer having a single (meth)acryloyloxy group, a difunctional (meth)acrylate monomer having two (meth)acryloyloxy groups, and a polyfunctional (meth)acrylate monomer having three or more (meth)acryloyloxy groups.
[0104] The (meth)acrylate oligomer may include a urethane (meth)acrylate oligomer, a polyester (meth)acrylate oligomer, an epoxy (meth)acrylate oligomer, and the like.
[0105] The polymerization initiator may cure the actinic radiation curable composition. The polymerization initiator may include at least one of a photocationic polymerization initiator and a photosensitizer.
[0106] As a photocationic polymerization initiator, any typical photocationic polymerization initiator known to those skilled in the art can be used. Specifically, the photocationic polymerization initiator may include an onium salt containing a cation and an anion. Examples of cations may include: diaryl iodonium, such as diphenyl iodonium, 4-methoxydiphenyl iodonium, bis(4-methylphenyl)iodonium, bis(4-tert-butylphenyl)iodonium, bis(dodecylphenyl)iodonium and (4-methylphenyl)[(4-(2-methylpropyl)phenyl)iodonium; triaryl sulfonium, such as triphenylsulfonium and diphenyl-4-thienyloxyphenylsulfonium; bis[4-(diphenylsulfonyl)-phenyl]sulfide, etc. Examples of anions may include hexafluorophosphate (PF6 - ), tetrafluoroborate (BF4- ), hexafluoroantimonate (SbF6 - ), hexafluoroarsenate (AsF6 - ) and hexachloroantimonate (SbCl6 - )wait.
[0107] As the photosensitizer, any typical photosensitizer known to those skilled in the art may be used. Specifically, the photosensitizer may include at least one of thioxanthone, phosphorus, triazine, acetophenone, benzophenone, benzoin and oxime photosensitizers.
[0108] The polymerization initiator may be present in an amount of about 0.01 parts by weight to about 10 parts by weight relative to 100 parts by weight of the actinic radiation curable compound. Within this range, the polymerization initiator may ensure sufficient curing of the composition to provide high mechanical strength and good adhesion to the polarizer.
[0109] The actinic radiation curable composition may further include typical additives such as silicone leveling agents, UV absorbers, antistatic agents, etc. The additives may be present in an amount of 0.01 parts by weight to about 1 part by weight relative to 100 parts by weight of the actinic radiation curable compound.
[0110] The thickness of the protective layer can be 5 μm to 200 μm, specifically 30 μm to 120 μm. When implemented by a protective film, the thickness of the first protective layer can be 50 μm to 100 μm, and when implemented by a protective coating, the thickness is 5 μm to 50 μm. Within this thickness range, the protective layer can be used in a light-emitting display.
[0111] although Figure 1 Not shown, a surface treatment layer may be further formed on at least one surface of the protective layer, such as a hard coating layer, an anti-fingerprint layer, an anti-reflection layer, a primer layer, etc. The hard coating layer, the anti-fingerprint layer, the anti-reflection layer, the primer layer, etc. may include layers formed by typical methods known to those skilled in the art.
[0112] In a structure where the protective layer is implemented by a protective film, a bonding layer may be further formed between the protective layer and the polarizer. The bonding layer may be formed by a typical adhesive for polarizing plates, such as a water-based adhesive, a photocurable adhesive, and a pressure-sensitive adhesive. However, in a structure where the protective layer is implemented by a protective coating, the bonding layer may be omitted.
[0113] The adhesive layer 130 is formed on one surface of the static dissipative coating layer 120 and adheres to the static dissipative coating layer 120 , and may attach the polarizing plate to the liquid crystal panel.
[0114] The thickness of the adhesive layer 130 may be 10 μm to 300 μm, for example 10 μm to 100 μm. Within this thickness range, the adhesive layer may be used in a polarizing plate.
[0115] The adhesive layer 130 may be formed of an adhesive composition including an adhesive resin. The adhesive resin may include at least one of a (meth) acrylic adhesive resin, a silicone adhesive resin, and an epoxy adhesive resin. Preferably, in consideration of an electrostatic dissipative coating, the adhesive resin includes a (meth) acrylic adhesive resin.
[0116] The adhesive composition may include a (meth)acrylic adhesive resin and a curing agent.
[0117] The (meth) acrylic binder resin may include a (meth) acrylic copolymer containing at least one of a hydroxyl group and a carboxylic acid group. The (meth) acrylic copolymer may be a copolymer of a monomer mixture including at least one of a hydroxyl-containing (meth) acrylic monomer and a carboxylic acid group-containing (meth) acrylic monomer; and at least one of an alkyl-containing (meth) acrylic monomer, an alicyclic group-containing (meth) acrylic monomer, a heteroalicyclic group-containing (meth) acrylic monomer, and an aromatic group-containing (meth) acrylic monomer. Preferably, the (meth) acrylic binder resin includes a (meth) acrylic ester copolymer having a carboxylic acid group.
[0118] The hydroxyl-containing (meth)acrylic monomer may include at least one of 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 1,4-cyclohexanedimethanol mono(meth)acrylate, 1-chloro-2-hydroxypropyl (meth)acrylate, diethylene glycol mono(meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, 4-hydroxycyclopentyl (meth)acrylate and 4-hydroxycyclohexyl (meth)acrylate.
[0119] The (meth)acrylic monomer containing a carboxylic acid group may include (meth)acrylic acid.
[0120] The alkyl-containing (meth) acrylic monomer may be an unsubstituted C1 to C 10 The (meth)acrylate of the alkyl group may include, for example, at least one of methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, and dodecyl (meth)acrylate.
[0121] The (meth) acrylic monomer containing alicyclic groups is a monomer containing C3 to C 20 The (meth)acrylate of the alicyclic group may include, for example, at least one of cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, and isobornyl (meth)acrylate.
[0122] The (meth)acrylic monomer containing a heteroalicyclic group may include a C3 to C4 monomer containing a heteroatom (nitrogen, oxygen or sulfur). 10 (Meth)acrylates of heteroalicyclic groups, specifically (meth)acryloylmorpholine.
[0123] In one embodiment, the (meth) acrylic copolymer can be a copolymer of a monomer mixture of a (meth) acrylic monomer containing a carboxylic acid group comprising 0.1wt% to 5wt%. For example, the monomer mixture can include 90wt% to 99.8wt% alkyl-containing (meth) acrylic monomers, 0.1wt% to 5.0wt% hydroxyl-containing (meth) acrylic monomers, and 0.1wt% to 5.0wt% carboxylic acid-containing (meth) acrylic monomers. Preferably, the monomer mixture includes 97.5wt% to 99.4wt% alkyl-containing (meth) acrylic monomers, 0.5wt% to 1.5wt% hydroxyl-containing (meth) acrylic monomers, and 0.1wt% to 1.0wt% carboxylic acid-containing (meth) acrylic monomers. Within this range, the adhesive composition can ensure good bonding strength of the adhesive layer to show good adhesion to the static dissipative coating.
[0124] The (meth) acrylic copolymer can be prepared by typical polymerization of a monomer mixture. The polymerization of the monomer mixture can be carried out by typical methods known to those skilled in the art. For example, the (meth) acrylic copolymer can be prepared by adding an initiator to the monomer mixture and then by typical polymerization of the monomer mixture (e.g., suspension polymerization, emulsion polymerization, solution polymerization, etc.). Here, the polymerization can be carried out at 50° C. to 70° C. for 6 to 10 hours. As an initiator, any typical initiator can be used, including an azo polymerization initiator and / or a peroxide polymerization initiator such as benzoyl peroxide or acetyl peroxide.
[0125] Curing agent is a typical curing agent, which is usually included in the adhesive composition. For example, the curing agent can include at least one of isocyanate curing agent, aziridine curing agent, epoxy curing agent and imide curing agent. Preferably, the curing agent is a mixture of isocyanate curing agent and aziridine curing agent.
[0126] The isocyanate curing agent may include a trifunctional or higher-functional (specifically tri- to hexafunctional) isocyanate curing agent. Specifically, the isocyanate curing agent may include one of the isocyanate monomers, such as a trifunctional isocyanate curing agent, including a trifunctional trimethylolpropane-modified toluene diisocyanate adduct, a trifunctional toluene diisocyanate trimer and a trimethylolpropane-modified xylene diisocyanate adduct, a hexafunctional trimethylolpropane-modified toluene diisocyanate, a hexafunctional isocyanurate-modified toluene diisocyanate, an isocyanate monomer, such as toluene diisocyanate, chlorophenylene diisocyanate, tetramethylene diisocyanate, xylylene diisocyanate, diphenylmethane diisocyanate and hydrogenated diphenylmethane diisocyanate, or an isocyanate compound produced by adding such an isocyanate monomer to trimethylolpropane; and a urethane prepolymer-type isocyanate produced by the addition reaction of an isocyanurate compound or an isocyanate biuret compound with a polyether polyol, a polyester polyol, an acrylic polyol, a polybutadiene polyol, a polyisoprene polyol, or the like. These may be used alone or as a mixture thereof.
[0127] The aziridine curing agent may be the aforementioned difunctional aziridine curing agent or trifunctional aziridine curing agent, such as trimethylolpropane tris(2-methyl-1-aziridine propionate), tris(1-aziridinyl)phosphine oxide, tris(2-methyl-1-aziridinyl)phosphine oxide, etc. Preferably, the aziridine curing agent includes a trifunctional aziridine curing agent.
[0128] The curing agent may be present in an amount of 5 parts by weight or less, specifically 0.01 to 1.5 parts by weight, more specifically 0.01 to 1 part by weight, relative to 100 parts by weight of the (meth) acrylic adhesive resin. Within this range, the curing agent can ensure the durability of the adhesive composition while reducing the aging time.
[0129] The adhesive composition may further include a silane coupling agent. The silane coupling agent may increase the adhesive strength of the adhesive layer relative to an adherend such as glass. The silane coupling agent may include typical silane coupling agents known to those skilled in the art. For example, the silane coupling agent may include at least one selected from the group consisting of: an epoxide silicon compound such as 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; a silicon compound containing a polymerizable unsaturated group such as vinyltrimethoxysilane, vinyltriethoxysilane, and (meth)acryloxypropyltrimethoxysilane; an amino group-containing silicon compound such as 3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, and N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane; and a mercapto group-containing silicon compound such as γ-mercaptopropyltrimethoxysilane, γ-mercaptopropyltriethoxysilane, γ-mercaptobutyltrimethoxysilane, and γ-mercaptopropylmethyldimethoxysilane, but is not limited thereto.
[0130] The silane coupling agent may be present in an amount of 0.01 to 5 parts by weight, specifically 0.01 to 2 parts by weight, relative to 100 parts by weight of the (meth) acrylic adhesive resin. Within this range, the adhesive composition can ensure good durability, prevent the adhesive layer from detaching under moisture resistance conditions, and the performance such as glass peel strength changes less over time. In particular, a silane coupling agent containing an epoxy group or a mercapto group can further improve this effect of the adhesive composition.
[0131] The adhesive composition may also include typical additives. The additives may include UV absorbers, antioxidants, adhesion imparting resins, plasticizers, modifying agents, etc. The additives may include typical additives known to those skilled in the art. Relative to 100 parts by weight of the (meth) acrylic adhesive resin, the additive may be present in an amount of 0.001 to 5 parts by weight, specifically 0.01 to 1 part by weight. Within this range, the additive may achieve its effect without affecting the performance of the adhesive film for polarizing plates.
[0132] The adhesive composition may have a viscosity of 1,000 cP to 4,000 cP at 25° C. Within this range, the adhesive composition may facilitate thickness adjustment of an adhesive layer, form an adhesive layer without generating spots, provide a uniform coating surface, and be suitable for rapid coating.
[0133] The adhesive composition may be applied to a predetermined thickness and then left to stand at 20° C. to 35° C. for 12 hours or more to form an adhesive layer.
[0134] The polarizing plate may have a thickness of 10 μm to 500 μm, for example, 50 μm to 300 μm. Within this range, the polarizing plate may be applied to optical displays.
[0135] although Figure 1 Although not shown in the figure, the polarizing plate may further include a release film (eg, a polyester release film surface-treated with a silicone material) attached to a lower surface of the adhesive layer.
[0136] An optical display according to one embodiment of the present invention may include a polarizing plate according to the present invention. For example, the optical display may include a liquid crystal display and an organic light emitting display, but is not limited thereto. An optical display according to an embodiment may include a liquid crystal display panel, a first polarizing plate formed on an upper surface of the liquid crystal display, a second polarizing plate formed on a lower surface of the liquid crystal display, and a backlight unit formed under the second polarizing plate, wherein at least one of the first and second polarizing plates may include a polarizing plate according to an embodiment of the present invention.
[0137] The liquid crystal display panel may adopt a twisted nematic (TN) mode, a vertical alignment (VA) mode, a patterned vertical alignment (PVA) mode, an IPS mode, or a super patterned vertical alignment (S-PVA) mode. In particular, the TN mode liquid crystal display panel may have an excellent effect of preventing light leakage.
[0138] In one embodiment, the optical display includes a liquid crystal panel, a first polarizing plate formed on the upper surface of the liquid crystal panel, a cover glass such as a window film formed on the upper surface of the first polarizing plate, and a second polarizing plate formed on the lower surface of the liquid crystal panel, wherein the first polarizing plate may include a polarizing plate according to the present invention. The polarizing plate according to the present invention may be stacked on the liquid crystal panel through an adhesive layer. The polarizing plate according to the present invention may be arranged on the view side of the optical display. The cover glass may be stacked on the first polarizing plate through an optically clear adhesive (OCA), but is not limited thereto. The second polarizing plate may be stacked thereon through a typical adhesive.
[0139] Subsequently, the present invention will be described in more detail with reference to some examples. It should be understood that these examples are provided for illustration only and are not to be construed in any way as limiting the present invention.
[0140] Preparation Example 1: Preparation of curable resin
[0141] 200g of polycaprolactone diol (weight average molecular weight: 2,000g / mol, Daicel Chemical Industries, Ltd.) was placed in a 1L reactor purged with nitrogen. Then, 105g of methylene diphenyl diisocyanate (MDI, BASF) and 0.5g of dibutyltin dilaurate (DBTDL) (S, Soken Co., Ltd.) were added thereto. In the reactor, the resulting mixture was stirred at 90°C for 30 minutes. While the mixture was stirred at a constant rate, 27g of dimethylolpropionic acid (Pestorp Co., Ltd.) was added thereto to provide ions, and 110g of N-methyl-2-pyrrolidine (NMP, Samchun Chemicals Co., Ltd.) was added to the mixture to dissolve the dimethylolpropionic acid. Then, the resulting mixture was placed in a reactor at 92°C for 5 hours.
[0142] The prepolymer obtained from the reactor was cooled to 75°C and 264g of methyl methacrylate (Aldrich GmbH) was added to the prepolymer. The obtained mixture was stirred at 75°C for 15 minutes and cooled to 25°C. Then, 20g of triethylamine (Junsei Co., Ltd.) was added to the mixture, and the mixture was placed at 25°C for 1 hour to neutralize. Subsequently, 65g of acrylic acid (Aldrich GmbH) was added to the obtained mixture, and then stirred. The resulting mixture was dispersed in distilled water. Then, ethylenediamine dissolved in distilled water was added to the obtained mixture to complete the polymerization reaction, and it was placed at 25°C for 2 hours, thereby obtaining a polyurethane acrylate solution with a carboxylic acid group as a curable resin (weight average molecular weight: about 4,000g / mol, solid content: 25%).
[0143] Preparation Example 2: Preparation of curable resin
[0144] 200g of polycaprolactone diol (weight average molecular weight: 2,000g / mol, Daicel Chemical Industries, Ltd.) was placed in a 1L reactor purged with nitrogen. Then, 105g of methylene diphenyl diisocyanate (MDI, BASF) and 0.5g of dibutyltin dilaurate (DBTDL) (S, Soken Co., Ltd.) were further added to the reactor. The resulting mixture was stirred at 90°C for 30 minutes in the reactor. While stirring the mixture at a constant rate, 27g of dimethylolpropionic acid (Pestorp Co., Ltd.) was added to the reactor to provide ions, and 110g of N-methyl-2-pyrrolidine (NMP, Samchun Chemicals Co., Ltd.) was added to the mixture to dissolve the dimethylolpropionic acid. Then, the resulting mixture was placed in a reactor at 92°C for 5 hours.
[0145] The prepolymer obtained from the reactor was cooled to 75°C and 264g of methyl methacrylate (Aldrich GmbH) was added to the prepolymer. The obtained mixture was stirred at 75°C for 15 minutes and cooled to 25°C. Then, 20g of triethylamine (Junsei Co., Ltd.) was added to the mixture, and the mixture was left at 25°C for 1 hour for neutralization. Then, 65g of acrylic acid (Aldrich GmbH) was added to the obtained mixture, followed by stirring. Then, ethylenediamine dissolved in distilled water was added to the obtained mixture to complete the polymerization reaction, and left at 25°C for 2 hours, thereby obtaining a polyurethane acrylate solution (weight average molecular weight: about 4,000g / mol, solid content: 25%) without a carboxylic acid group as a curable resin.
[0146] The details of the components used in the following Examples and Comparative Examples are as follows:
[0147] (A) Curable resin: (A1) Preparation Example 1 and (A2) Preparation Example 2 were used.
[0148] (B) Aziridine curing agent
[0149] (B1) Bifunctional aziridine curing agent: N,N′-(methylenedi-p-phenylene)bis(aziridine-1-carboxamide) (HDU-P25, solid content: 25 wt %, blocked isocyanate aziridine, Sthal) was used.
[0150] (B2) Trifunctional aziridine curing agent: trimethylolpropane tris(2-methyl-1-aziridine propionate) (CL-467, solid content: 99 wt %, Menadiona Europe) was used.
[0151] (C) Conductive polymer liquid dispersion: PEDOT:PSS water-based liquid dispersion (Baytron PH, Bayer) was used.
[0152] Example 1
[0153] 5 g of the conductive polymer liquid dispersion was added to 35 g of a mixed solvent obtained by mixing distilled water and ethanol at a weight ratio of 1:1, followed by stirring at room temperature for 10 minutes. Then, 80 g of the curable resin (A1) of Preparation Example 1 was added thereto and stirred, and 1.2 g of a difunctional aziridine curing agent (B1) was further added thereto and stirred at room temperature for 30 minutes, thereby preparing a composition for a static dissipative coating.
[0154] Table 1 (unit: parts by weight) shows the amount of the difunctional aziridine curing agent relative to 100 parts by weight of the curable resin and the conductive polymer in the composition for static dissipative coating.
[0155] Examples 2 to 5
[0156] A composition for static dissipative coating was prepared in the same manner as in Example 1, except for the amount of the difunctional aziridine curing agent.
[0157] Comparative Example 1
[0158] A composition for static dissipative coating was prepared in the same manner as in Example 1, except that the difunctional aziridine curing agent was not added.
[0159] Comparative Example 2
[0160] A composition for static dissipative coating was prepared in the same manner as in Example 1, except that the curable resin (A2) of Preparation Example 2 was used instead of the curable resin (A1) in Preparation Example 1.
[0161] Comparative Example 3
[0162] A composition for static dissipative coating was prepared in the same manner as in Example 1, except that a trifunctional aziridine curing agent (B2) was used instead of the difunctional aziridine curing agent (B1).
[0163]
[0164]
[0165] *All components are based on solids content
[0166] The compositions for static dissipative coating prepared in Examples and Comparative Examples were evaluated for properties with respect to Table 2 and the results are shown in Table 2. An acrylic composition for an adhesive layer for performance evaluation was prepared by Preparation Example 3.
[0167] Preparation Example 3: Preparation of acrylic composition for adhesive layer
[0168] A monomer mixture containing 63 parts by weight of n-butyl acrylate (BA), 34 parts by weight of methyl acrylate (MA), 1 part by weight of 2-hydroxyethyl methacrylate (2-HEMA) and 2 parts by weight of acrylic acid (AA) and 100 parts by weight of ethyl acetate (EA) as a solvent were placed in a 1L reaction vessel, which was provided with a cooler for temperature regulation and circulated with nitrogen. Thereafter, nitrogen was added to the reactor for 1 hour to remove oxygen, and the reactor was maintained at 62°C. The monomer mixture was uniformly stirred in the reactor, 0.07 parts by weight of azobisisobutyronitrile (AIBN) as a reaction initiator was added to the mixture, and the mixture was left for 8 hours, thereby obtaining a (meth) acrylic copolymer (weight average molecular weight: 800,000 to 1,100,000, PDI: 4.0, glass transition temperature: -31°C).
[0169] 100 parts by weight of the prepared acrylic copolymer, 0.5 parts by weight of trimethylolpropane tris(2-methyl-1-aziridine propionate) (CL-467, solid content: 99 wt%, Menadiona Europe) as a trifunctional aziridine curing agent, 0.02 parts by weight of an isocyanate curing agent (TD-75, Soken) and 0.063 parts by weight of a silane coupling agent (KBM-403) were mixed, then diluted to a concentration of 20% with methyl ethyl ketone as a solvent and stirred for 30 minutes, thereby preparing an acrylic composition for an adhesive layer.
[0170] Performance Evaluation
[0171] (1) Presence of adhesion: On a PET release film, each of the compositions for static dissipative coating prepared in Examples and Comparative Examples was deposited to a thickness of 500 μm and dried at 80° C. for 2 minutes, thereby preparing a specimen having a thickness of 5.0 μm. When the specimen was touched by hand, a specimen having adhesion was evaluated as an adhesion specimen, and a specimen having no adhesion was evaluated as a non-adhesion specimen.
[0172] (2) Pot life: The initial standing time of the compositions for static dissipative coatings prepared in the Examples and Comparative Examples was measured. For the initial standing time, the difference in the common logarithm of the surface resistance of the compositions calculated by Formula 2 was 2Ω / □:
[0173] <Formula 2>
[0174] |log 10 A-log 10 B|
[0175] Wherein, B is the surface resistance value (unit: Ω / □) of the composition for static dissipative coating measured on a 0.1 μm thick first coating layer under the conditions of 23° C. and 55% RH, wherein the first coating layer is obtained by coating 100 g of the composition on a polarizing film to a thickness of 10 μm, followed by drying at 80° C. for 2 minutes, and A is the surface resistance value (unit: Ω / □) of the composition for static dissipative coating measured on a 0.1 μm thick second coating layer under the conditions of 23° C. and 55% RH, wherein the second coating layer is obtained by placing 100 g of the composition at 25° C. for a predetermined period of time and coating the composition on a polarizing film to a thickness of 10 μm, followed by drying at 80° C. for 2 minutes.
[0176] Here, the polarizing film is a polarizing film of a three-layer structure formed by stacking triacetyl cellulose films on both surfaces of a polarizer formed of a polyvinyl alcohol resin. The surface resistance is measured using SIMCO ST-3 at 23°C and 55% RH. Generally, since an initial standing time of 24 hours or more is not required, an initial standing time of 24 hours or more is not measured.
[0177] (3) Surface resistance change rate: A three-layer structure polarizing film was prepared by stacking a triacetyl cellulose film (film thickness: 40 μm, Konica film) on both surfaces of a polarizer formed of a polyvinyl alcohol resin. On one surface of the triacetyl cellulose film, each of the compositions for static dissipative coating prepared in the examples and comparative examples was applied to a thickness of 0.1 μm to 0.2 μm, followed by drying at 80°C for 2 minutes, to form a 10 μm thick static dissipative coating on one surface of the triacetyl cellulose film. An adhesive layer (thickness: 20 μm) formed of the acrylic adhesive of Preparation Example 3 was formed on one surface of the static dissipative coating, thereby preparing a polarizing plate in which the polarizing film, the static dissipative coating and the adhesive layer were stacked in the stated order.
[0178] The initial surface resistance value (R0, unit: Ω / □) was measured on the adhesive layer of the polarizing plate at 23°C and 55% RH using SIMCO ST-3. Thereafter, the polarizing plate was placed at 60°C and 95% RH for 500 hours, and the surface resistance (R1, unit: Ω / □) was measured at 23° under the same conditions. The surface resistance change rate was calculated by Equation 1:
[0179] <Equation 1>
[0180] Surface resistance change rate = |R1-R0| / R0 x 100
[0181] The lower surface resistance change rate indicates that the polarizing plate has higher reliability by preventing degradation of the static electricity dissipation function even after being left for a long time.
[0182] (4) Durability under high temperature / high humidity conditions: A polarizing plate was manufactured in the same manner as in (3). Two samples were prepared by cutting the manufactured polarizing plate to a size of 400 mm x 200 mm. The samples were attached to both surfaces of a glass substrate having a size of 410 mm x 210 mm x 0.7 mm (length x width x thickness) so that the absorption axes of the polarizers were perpendicular to each other, and placed at 60°C and 95% RH for 500 hours, and then evaluated at room temperature according to the following criteria:
[0183] ◎: No appearance changes such as slight wrinkling, delamination or blistering between the static dissipative coating and the adhesive layer
[0184] △: Micro wrinkles, delamination or bubbles with a maximum length of 300μm or less are generated between the static dissipative coating and the adhesive layer
[0185] X: Minor wrinkles, delamination or bubbles with a minimum length greater than 300 μm are generated between the static dissipative coating and the adhesive layer
[0186]
[0187]
[0188] From the results shown in Table 2, it can be seen that although the composition for static dissipative coating of the embodiment is non-adhesive, it has a long application life to provide good storage stability and improve workability, a low surface resistance change rate, and good durability under high temperature / high humidity conditions.
[0189] In contrast, the compositions of Comparative Examples 1 and 2, which did not include a curable resin having a carboxylic acid group or a bifunctional aziridine curing agent, had a high rate of change in surface resistance and exhibited poor durability. The composition of Comparative Example 3, which included a trifunctional aziridine curing agent instead of a bifunctional aziridine curing agent, had a short pot life, provided poor storage stability, and exhibited poor durability under high temperature / high humidity conditions.
[0190] It should be understood that various modifications, changes, variations and equivalent embodiments may be made by those skilled in the art without departing from the spirit and scope of the present invention.
Claims
1. A composition for an electrostatic dissipative coating, comprising: a curable resin having a carboxylic acid group, a difunctional aziridine curing agent, and a conductive polymer, wherein the curable resin comprises urethane bonds, in, The composition comprises 80 to 99 parts by weight of the curable resin having a carboxylic acid group, 1 to 20 parts by weight of the conductive polymer, and 0.0005 to 0.02 parts by weight of the bifunctional aziridine curing agent, relative to 100 parts by weight of the curable resin having a carboxylic acid group and the conductive polymer. The curable resin includes polyurethane (meth) acrylate containing a carboxylic acid group.
2. The composition for a static dissipative coating according to claim 1, wherein the composition for a static dissipative coating has an initial standing time of 24 hours or more, and for the initial standing time, the difference between the common logarithms of the surface resistance expressed by the following formula 2 is 2Ω / □ or more: <Formula 2> |log 10 A-log 10 B| Wherein B is the surface resistance value in Ω / □ of the composition for static dissipative coating measured on a first coating layer of 0.1 μm thick under the conditions of 23°C and 55% RH, wherein the first coating layer is obtained by coating 100 g of the composition on a polarizing film to a thickness of 10 μm, followed by drying at 80°C for 2 minutes, and A is the surface resistance value in Ω / □ of the composition for static dissipative coating measured on a second coating layer of 0.1 μm thick under the conditions of 23°C and 55% RH, wherein the second coating layer is obtained by placing 100 g of the composition at 25°C for a predetermined period of time, and coating the composition on a polarizing film to a thickness of 10 μm, followed by drying at 80°C for 2 minutes. 3 . The composition for static dissipative coating according to claim 1 , wherein the curable resin has an acid value of 1 to 30 mg KOH / g.
4. The composition for static dissipative coating according to claim 1, wherein the curable resin is a heat-curable resin having a (meth)acrylate group.
5. The composition for static dissipative coating according to claim 1, wherein the conductive polymer is doped with a water-based dopant.
6. The composition for static dissipative coating according to claim 1, wherein the conductive polymer comprises at least one of polyacetylene, poly(p-phenylene), polythiophene, poly(3,4-ethylenedioxythiophene), polypyrrole, poly(p-phenylene sulfide), poly(p-phenylene vinylene), poly(thienylene vinylene) and polyaniline.
7. The composition for static dissipative coating according to claim 1, wherein the bifunctional aziridine curing agent comprises at least one of N,N'-(methylenediphenylene)bis(aziridine-1-carboxamide) and N,N'-hexamethylene 1,6-bis(1-aziridinecarboxamide).
8. The composition for a static dissipative coating according to claim 1, wherein the composition for a static dissipative coating is a water-based composition comprising a water-based solvent.
9. The composition for static dissipative coating according to claim 8, wherein the water-based solvent is (i) water, or (ii) a mixed solvent comprising water and at least one of alcohol and dimethyl sulfoxide.
10. A polarizing plate, comprising: polarizing film; forming a static dissipative coating on the polarizing film; and forming an adhesive layer on the static dissipative coating, wherein the static dissipative coating is formed from a composition for a static dissipative coating, The composition comprises a curable resin having a carboxylic acid group, a bifunctional aziridine curing agent, and a conductive polymer. wherein the polarizing plate has a surface resistance variation rate of 5% or less calculated by Equation 1: Surface resistance change rate = |R1-R0| / R0 x 100 wherein R0 is an initial surface resistance value in Ω / □ measured on the adhesive layer of the polarizing plate under the conditions of 23° C. and 55% RH, and R1 is a surface resistance value in Ω / □ measured on the adhesive layer of the polarizing plate at room temperature by the same method as above after the polarizing plate is left under conditions of 60° C. and 95% RH for 500 hours, Wherein, relative to 100 parts by weight of the curable resin having a carboxylic acid group and the conductive polymer, the composition comprises 80 parts by weight to 99 parts by weight of the curable resin having a carboxylic acid group, 1 part by weight to 20 parts by weight of the conductive polymer, and 0.0005 parts by weight to 0.02 parts by weight of the bifunctional aziridine curing agent, The curable resin includes polyurethane (meth) acrylate containing a carboxylic acid group. The polarizing plate according to claim 10 , wherein the static dissipative coating is directly formed on the polarizing film. 12 . The polarizing plate of claim 10 , wherein the static dissipative coating has a thickness of 1 nm to 10 μm. 13 . The polarizing plate of claim 10 , wherein the adhesive layer is formed of an adhesive composition including a (meth)acrylate copolymer having a carboxylic acid group and a curing agent.
14. An optical display comprising the polarizing plate according to claim 10.
Citation Information
Patent Citations
Antistatic protection films for display
KR100760978B1
Pressure-sensitive adhesive composition, protective film, polarizer and liquid crystal display comprising the same
CN101910346A
Thermosetting type antistatic coating agent, cured coating therefor and plastic film therefor
CN106167662A
Pressure-sensitive adhesive composition, pressure-sensitive adhesive film, polarizer and liquid crystal display
KR1020100008748A